(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
At present, all things have become very compact, in case of communication they can be defined by different attributes like - digital documents, internet Medias, tele-medicines etc. People have become internet dependent these days. Now a days communication over the internet like – Skype, messengers, g-talk are very familiar tools for chatting. Facebook is also an all-in-one communication media these days. But these software applications that most of the people use need more bandwidth. As a number of enormous internets using people are increasing day by day for that a proper way is needed to control and distribute bandwidth within a conjugated network nodes or network clouds. These days’ people prefer video chatting for more secured and dedicated communication. To send videos as data packets consider the topologies such as- mesh, bus, ring, star, hybrid within the communication networks which uses unlimited bandwidth results a huge wastage but creates a problem for the higher growth of internet users. Thinking of this a controlled algorithm for bandwidth optimization as well as bandwidth management is developed. This algorithm is developed considering a video communication system that has the ability of running PABX, Fax, video via-web conference, video presentation for a defined time through the creation of admin defined extensions. The algorithm has developed considering a local LAN (no internet) and can process user defined data by checking the processing capacity of a processor that ensures 0% drop probability of packets which make it special. The overall mechanism shows better possibilities as an estimation scheme throughout the network nodes to ensure the administrators to design a proper and better network for any distributed network architectures. After evaluating the results, it is assured that this topology works better than any other existing topologies for a distributed system that follows M/M/1 queuing theory.